Disrupting nature? A critical analysis of the genderless toilet drive represented in South African newspapers - Rachel Moyo; Sphesihle Khanyile (SIMULACRA: JURNAL SOSIOLOGI, 2023)
Global cultures and imperialist Western ways of being and doing pervasively penetrate and influence societies and individuals, overarching the nations at the bottom of development. This globality operates unidirectionally, biased toward the Western gravity of power, excluding, disenfranchising, erasing, and debasing the values of the global South’s peripheries. Consequently, the theory of globalization has focused on how localized groups in subaltern developing countries respond to the weighty forces of globalism. This paper presents a critical analysis that explores the omnipotent ideologicalhegemonic power of the media to cultivate, enculturate, and superimpose values normative to the ethos of global culture. We employ critical discourse analysis to analyze seven selected newspapers that reported on a draft proposal by the Department of Basic Education that envisions the eradication of gender labels through the imposition of genderless toilets in South African schools. Critical reading of the newspaper articles demonstrated clear Afrocentric pushbacks; other counternarratives displayed the societal incongruity of such a vision. The media frames corresponded to audience frames that vehemently rejected the unisex toilet proposition. The frames continue to invite readers to question the redefinition of gender identities and performances that promote global cultural values that supposedly disrupt nature.